Conveying the message of Islam :|mosque sermons by women preachers - Dincer, Hümeyra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis is a study of Islamic sermons conveyed in mosques by women preachers hired by the Directorate of Religious Affairs for the congregation of women. This study is an attempt to see how providing positions for women in public spaces as preachers and supporting the women population with religious instructions is actually undertaken by the actors in the context of the state’s aim to expand religion. This thesis focuses on the relation between the space in which the sermons are delivered, the content of the sermons and the narrative structures used to transmit this content. Their narratives, in this sense, constitute the basis of the research through which I attempt to grasp how the notion of “living a Muslim life” is constructed and maintained in today’s world and how religious beliefs, rituals and ethics are transmitted by religious specialists to Muslim women. Despite the fact that scholars have undertaken numerous studies about the relation between the state and religion by focusing on the Directorate, scant attention has been paid to the ways this relation is exercised in the everyday. The actors and the contexts in which religious practices have been conveyed to the population at large, the means available to these actors and the limitations of these processes of transmission have not been the object of analysis. The thesis is made up of three main chapters that constitute the three important dimensions of sermons: the space of narration, the content of the narrative and narrative style.
Keywords: Islamic preaching -- Turkey.; Muslim women -- Religious life -- Turkey.; Women in Islam -- Turkey.